Correction: Autism spectrum disorder diagnosis using fractal and non-fractal-based functional connectivity analysis and machine learning methods (Neural Computing and Applications, (2024), 36, 20, (12565-12585), 10.1007/s00521-024-09770-3) - Rakshe C.; Kunneth S.; Sundaram S.; Murugappan M.; Ronickom J.F.A. (My University, 2025)
The Acknowledgements section was missing from this article and should have read ‘This research received support from the Science and Engineering Research Board through the Start-up Research Grant (SRG) scheme (SRG/2021/002289). The authors also acknowledge the PARAM Shivay supercomputer facility at IIT BHU, Varanasi, India, for their valuable assistance during this study’. The original article has been corrected. © The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.